A method study on Ginger Bread Corporation - Estacio-David, Joseph Vincent (College of Engineering, 2000)
For a company to be successful, it has to succeed in its key result areas. For manufacturing companies, one of those key result areas is production. The objective of this study is to apply methods engineering concepts and systems and procedures concepts to a real-life production system employing various productivity and improvement techniques. The company under study is a bread manufacturing firm that was established in 1991. Its plant is located in Quezon City and mainly caters to fastfood chains and bakeries. Using streamline analysis, four core problems were arrived at: a) inefficient inventory management; b) no standard time; c) inefficient plant layout; and d) lax sanitation implementation. By solving these four core problems, an improvement in the efficiency of the production process of the company is to be expected. Minor problems will ultimately be answered with the solution of these major problems. By using various methods engineering techniques, the researchers recommended a number of alternatives for the company to employ. First, a change in the layout reduces the skills level required for the operation thus inappropriate movements and material flow would be avoided. It would also be beneficial to determine which workers work below or above the time standards set since it can pinpoint which workers need further training. A defined, orderly and nonhaphazardly method of product packaging was also suggested since it was proven that a systematic packaging process could save the company time by at most 40.5%. Regarding the inventory management system of the company, an increased coordination between the warehouse and production personnel would result to less occurrences of shortages in raw materials. A manual of specific guidelines is also good for the company to ensure continuity of operations regarding stock replenishment. Management should also be stricter with regards to the sanitation problem to ensure better quality and standards of its products. A lot can be further studies on the methods engineering framework of the company. One of which is to determine the exact economic order quantity that is appropriate for them. Another is the balancing of work schedules in order to get the most out of its workers. Lastly, conducting times studies on their other products will greatly help the company in improving its entire production system by not focusing on just one element.